“DISCURSIVE ANALYSIS OF ARCHITECTURAL AND CONSTRUCTION LANGUAGE UNITS IN ENGLISH AND UZBEK.” - Burxonov Baxodirjon Botirali o‘g‘li (Web of Journals Publishing, 2025)
Since discourse serves as a means of carrying out a particular act of communication, communicative goals are often expressed through a variety of linguistic and non-linguistic tools, frequently of a professional orientation. In this process, the adequacy of the interlocutors’ speech behavior is evaluated, and the success or failure of discursive interaction, as well as the achievement or non-achievement of communicative objectives, is determined. In this respect, discursive competence constitutes an essential component. Communicative competence, in turn, encompasses domain-specific spheres, situations, and topics of interaction, professionally oriented texts, cross-linguistic country-specific and socio-cultural knowledge, all of which reveal verbal communication skills and the communicative and intellectual abilities of the participants.
Keywords: Architectural construction, professional and occupational communication, architectural theory, technology, and industry